THE CONCEPT OF EMPIRICISM IN THE RAVADA BUDDHIST PHILOSOPHY - Abhiratato, Phramaha Jinkamol; Thongpan, Suwin; Candajoto, Phra Ritthichai; Thongjam, Rattana (Journal of Graduate MCU KhonKaen Campus, 2021)
This academic paper aims to present the concept of empiricism in Theravada Buddhist philosophy. Which found that empiricism was a quest for knowledge And the truth inside and out With self-access through the relationship between the internal sense (Ajjhattikayatana) and external senses (Bahirayatana) and Buddhist philosophy, the scope of knowledge is divided into two levels: (1) Mundance knowledge aims for peaceful daily life (2) Supermundance knowledge. Streak Whose goal is to break free from desires and attain Nirvana